2010
DOI: 10.1002/ca.21088
|View full text |Cite
|
Sign up to set email alerts
|

Extracardiac coronary arterial anastomoses

Abstract: The collateral arterial circulation of the heart has been extensively studied. However, less attention has been paid to extracardiac anastomoses, which may also be of significant clinical importance. In this review, we will describe the most common types of these anastomoses, which include bronchial to coronary arteries and internal thoracic to coronary arteries. In a much lesser degree, anastomoses between coronary arteries and pericardiacophrenic branches of the internal thoracic arteries, anterior mediastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
24
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 29 publications
1
24
1
Order By: Relevance
“…Prior observations have reported extra-cardiac collaterals arising from the left and right internal mammary arteries to LAD and to RCA and from bronchial arteries to RCA through pericardial branches [3,4]. This reported case is interesting for several reasons: It clearly demonstrates the presence of extra-cardiac collaterals.…”
Section: Commentsmentioning
confidence: 50%
See 1 more Smart Citation
“…Prior observations have reported extra-cardiac collaterals arising from the left and right internal mammary arteries to LAD and to RCA and from bronchial arteries to RCA through pericardial branches [3,4]. This reported case is interesting for several reasons: It clearly demonstrates the presence of extra-cardiac collaterals.…”
Section: Commentsmentioning
confidence: 50%
“…Extra-cardiac collaterals to the coronary arteries are not rare and have been reported in 10-20% of cases, but they are usually small and their flow is limited [3]. According to available literature, this is the first reported case of a functional extra-cardiac communication to a normal RCA.…”
Section: Commentsmentioning
confidence: 77%
“…1 Clinically, 1 case report using scintigraphy showed that RIMA to RCA collateral circulation with proximal RCA occlusion sufficiently perfused the RCA. 2 Another recent clinical study evaluated the function of naturally existing internal mammary-to-coronary artery bypasses and their quantitative effects on myocardial ischemia.…”
mentioning
confidence: 99%
“…1 By injecting a colloidal suspension of carbon particles to the coronary arteries at autopsy, 1 those studies found that the largest arteries was the pericardiacophrenic branches of internal mammary arteries. Other arteries, such as the anterior mediastinal, pericardial, bronchial, superior, and inferior phrenic, and intercostal and esophageal branches of the aorta were described as extracardiac arteries anastomosed with coronary arteries.…”
mentioning
confidence: 99%
See 1 more Smart Citation